Bailing Out The World's Poorest - Ravallion, Martin, 1952- 1952- (The World Bank, 2008)
While the 2008 financial crisis is global in nature, it is likely to have heterogeneous welfare impacts within the developing world, with some countries, and some people, more vulnerable than others. It also threatens to have lasting impacts for some of those affected, notably through the nutrition and schooling of children in poor families. These features point to the need for a differentiated social policy response, aiming to provide rapid income support to those in most need, while preserving the key physical and human assets of poor people and their communities. The paper points out some mistakes in past crisis responses and identifies key design features for safety net programs that can help compensate for the likely welfare losses in the short-term while also promoting longer-term recovery